COMPARATIVE ANALYSIS OF DECISION SUPPORT SYSTEMS USING THE FUZZY TAHANI AND WASPAS METHODS IN SELECTING TOURISM PLACES TO VISIT IN MAKASSAR - Satriawaty Mallu; Saharuddin (Nusantara Hasana Journal, 2023)
The selection of tourist attractions to be visited, especially the Makassar area requires several reasons, to make a decision which area to visit, several things need to be considered, besides that a Decision Support System is needed to give the best results. The system used is not just one in order to provide more accurate results. Analysis of the Decision Support System to choose the best tourist attractions in Makassar uses two methods, namely: the FUZZY Tahani Method and the WASPAS Method. The results of the analysis provide the best method using the same criteria, then the selection of tourist attractions to be visited in Makassar City. Based on the analysis between the The FUZZY Tahani Method and the WASPAS Method in selecting tourist attractions to be visited in Makassar City, in this case the use of the FUZZY Tahani Method is more appropriate. The object of his research is the decision support system for selection of tourist attractions to be visited. The results of his research showed that in The selection of tourist attractions to be visited using the FUZZY Tahani and WASPAS methods the same results were obtained for the best ranking, A7, but there were differences in the results for the next ranking.